Material Flow and Economic Analysis of Wantilan Recycling Center Promoting Circular Economy Principles - Satori, Mohamad; Hindersah, Hilwati; Burhanudin, Hani; Januarita, Ratna; Purnamasari, Pupung; Hernawati, Riza; Patricia, Vinda Maharani; Miftahadi, Machmuddin Fitra (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Waste is increasingly recognized not just as an environmental challenge but also as an economic opportunity, particularly in developing countries like Indonesia where it can help alleviate employment shortages. This study explores the dual role of waste as both a tradable commodity driven by industrial demands for raw materials, including primary substances, additives, and Refuse Derived Fuel (RDF), and as a means of reducing environmental impact. This phenomenon is important and interesting because it can have a positive impact both in terms of reducing waste, saving natural resources, and as an economic opportunity for society. This study aims to examine the potential of waste that can be utilized as a resource on the one hand and reduce the potential for pollution on the other. The study used the Material Flow Analysis (MFA) method with the Circular Economy principle and used an action research approach to redesign the waste processing system. The results of this study indicate that the current system only manages 34% of the total waste generation and only 4% can be reused with sales of IDR 97.9 million per year. With the development of a new system, the waste managed is 60% with the economic potential generated of 1.08 billion per year.